2021
DOI: 10.1016/j.scog.2021.100205
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive discrepancies, motivation and subjective well-being in people with schizophrenia

Abstract: Research indicates that people with schizophrenia often achieve similar levels of subjective well-being (SWB) compared to healthy controls despite prominent symptomatology and significant functional difficulties. Furthermore, compared to healthy controls, young-adult people with schizophrenia differ in the relative importance they place on values, or guiding life principles, associated with educational and occupational success ( openness to change ), suggesting that changing motivations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…These brain areas overlap with the areas of medical pathology of cognitive function in a large area, indicating that schizophrenia will mainly lead to the imbalance of cognitive function. This also proved that our study is consistent with medical judgment [14] .…”
Section: Visualizationsupporting
confidence: 90%
“…These brain areas overlap with the areas of medical pathology of cognitive function in a large area, indicating that schizophrenia will mainly lead to the imbalance of cognitive function. This also proved that our study is consistent with medical judgment [14] .…”
Section: Visualizationsupporting
confidence: 90%
“…Hospitalization is a highly recommended treatment for schizophrenic patients, since mental health professionals such as psychiatrists, clinical psychologists, and nurses can work together to provide the necessary psychiatric care and monitor patient health development (Hooley et al, 2018). Previous studies have found that through psychiatric treatment in hospitals, subjective well-being in schizophrenic patients can be improved by optimizing antipsychotic treatment (Vothknecht et al, 2011); maximizing psychological interventions such as by using a positive psychological approach (Valiente et al, 2019); defining values; and developing the selfefficacy of patients (Krzyzanowski et al, 2021).…”
Section: Introductionmentioning
confidence: 99%